Studi fenomenologi: Pengalaman pengelolaan keuangan keluarga kelas menengah di Kelurahan Petung Kabupaten Penajam Paser Utara - Aisyah, Salwa Nurul; Reza, Reza; Riyadi, Riyo; Sudarman, Sudarman (Journal of Economics Research and Policy Studies, 2025)
Financial management within families is crucial for maintaining household economic stability, particularly for middle-class families. Financial management within families is a skill that every family must possess, as failing to manage their finances effectively can result in expenses exceeding their income. Therefore, this study aims to interpret each action from the experiences of middle-class families in managing household finances and to identify and analyse the main challenges faced as well as the strategies implemented by middle-class families in Petung Village in financial management. The research design employed is qualitative, with a phenomenological approach, utilising data collection methods that include interviews and observations. The data analysis stages used are data condensation, data presentation, conclusion drawing, and verification. Based on the findings regarding middle-class families in Petung Village, it was revealed that their understanding of financial management is already quite good, and they can adapt to changes in the economic situation. Although some families do not regularly record their income and expenses, overall, family financial management is functioning smoothly. However, it is hoped that middle-class families in Petung Village can improve their financial management through the guidelines set by the Financial Services Authority (OJK)